Aspectos psicossociais do trabalho e transtorno mentais comuns entre trabalhadores informais feirantes - Mascarenhas, Morgana Santana (2014)
Informal work is characterized by low productivity activities, unstable employment, low wages, hand disqualified work and lack of benefits and social security. In this group are the vendors. The working process of the fairground structure in inadequate and precarious environmental and organizational conditions that can have a negative impact on physical and mental health, causing damage, among them the mental illness. The psychosocial aspects of work have been identified as important occupational stressors, with significant impacts on the mental health of workers. This study aimed to evaluate the association between psychosocial aspects of work and the occurrence of Common Mental Disorders among fairground workers with informal work contracts. This is a cross-sectional study with a sample of 774 fairground workers in the urban area of the city of Feira de Santana, Bahia. A questionnaire was used with questions on sociodemographic characteristics, professional job characteristics, psychosocial aspects of work and mental health. To measure psychosocial aspects of work used the Job Content Questionnaire (JCQ); and to assess Common Mental Disorders was used the Self-Reporting Questionnaire (SRQ-20). We conducted univariate and bivariate and multivariate logistic regression through the Multiple analysis. The overall prevalence of CMD in the fairground was 32.4%. CMD were associated sociodemographic characteristics (gender, age, marital status, low level of education, have children, low monthly income and lack of practice of leisure activity), occupational (insert age at work and exposure time, days work / week, time pressure and productivity requirement) and for the desktop. Higher prevalence of mental disorders were observed in high-strain groups (42.8%) and active work (34.8%), while the prevalence in low strain was 28.2%. Findings obtained in the analysis of multiple logistic regression revealed association between the group of high strain and mental disorders. Workers in high strain showed higher prevalence of CMD than the low strain group, after adjustment for sex, children, old who started working, noise presence in the workplace and leisure activities. The results showed that the disorders constitute a major public health issue affecting a significant portion of marketer workers.